Before He Hunts (A Mackenzie White Mystery-Book 8) - Blake, Pierce (Lukeman Literary, 2018)
From Blake Pierce, bestselling author of ONCE GONE (a #1 bestseller with over 900 five star reviews), comes book #8 in the heart-pounding Mackenzie White mystery series. In BEFORE HE HUNTS (A Mackenzie White Mystery-Book 8), victims are turning up dead in FBI Special Agent Mackenzie White's home state of Nebraska-all shot in the back of the head, and all bearing the card "Barker Antiques." The same card her father's murderer left on his body years ago. With a sudden urgency in the present, the time has finally come for Mackenzie to face her ghosts, to face her darkest past, and to find her father's killer. But her trip back down memory lane may take her to places she'd rather not see, and to discoveries she'd rather not find. She finds herself playing cat and mouse with a killer more sinister than she could imagine, and with her fragile psyche collapsing, this case, of all of them, may be the one that does her in for good. A dark psychological thriller with heart-pounding suspense, BEFORE HE HUNTS is book #8 in a riveting new series-with a beloved new character-that will leave you turning pages late into the night. Also available by Blake Pierce is ONCE GONE (A Riley Paige mystery-Book #1), a #1 bestseller with over 900 five star reviews-and a free download!
Keywords: Krimi, detektivky